Fatty Liver Increases the Association of Metabolic Syndrome With Diabetes and Atherosclerosis - Juárez-Rojas, Juan G. (American Diabetes Association, 2013)
OBJECTIVE: To analyze the participation of fatty liver (FL) in the association of metabolic syndrome (MS) with type 2 diabetes and coronary artery calcification (CAC). RESEARCH DESIGN AND METHODS: A total of 765 subjects (52% women) aged 30 to 75 years without clinical atherosclerosis were included in this study. MS was defined in accordance with the Adult Treatment Panel III (ATPIII) guidelines, while FL and CAC were identified by computed tomography. RESULTS: There were increasing frequencies of type 2 diabetes and CAC in all three groups: control, MS without FL, and MS plus FL. Multivariable-adjusted logistic regression analyses showed that FL increased the association of MS with type 2 diabetes in both women [odds ratio 10.6 (95% CI 3.4–33.7)] and men [12.1 (4.1–36.1)]. In women, FL also increased the association of MS with CAC [2.34 (1.07–5.12)]. CONCLUSIONS: FL increases the association of MS with type 2 diabetes and subclinical atherosclerosis.